Light-absorbing heat-resistant plastic masterbatch containing mica iron oxide and preparation method thereof

By modifying and covering the mica iron oxide, the problem of poor compatibility with polyolefin plastics is solved, and the mechanical properties, high temperature resistance and ultraviolet light absorption and anti-aging properties of the plastic are significantly improved.

CN116496574BActive Publication Date: 2025-04-25ANHUI NEWYADA TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310625344.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2025-04-25
Estimated Expiration
2043-05-30

AI Technical Summary

Technical Problem

In the prior art, the compatibility of mica iron oxide and polyolefin plastics is poor, resulting in the need to improve the mechanical properties of the plastic and the resistance to high temperature and ultraviolet light absorption and anti-aging properties.

Method used

By modifying the mica iron oxide, including ball milling into powder and reacting with KH-570, the surface of the mica iron oxide is grafted into siloxane bonds, and its dispersion in polypropylene is improved. At the same time, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole is used to react with acryloyl chloride to form a mica iron oxide additive with polyolefin coating to enhance its crosslinkability with polypropylene.

Benefits of technology

The dispersion and crosslinking properties of mica iron oxide in polyolefin plastics are improved, and the mechanical properties, high temperature resistance and ultraviolet light absorption and anti-aging properties of the plastics are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004256857600000031
    Figure BDA0004256857600000031
  • Figure BDA0004256857600000041
    Figure BDA0004256857600000041
  • Figure BDA0004256857600000051
    Figure BDA0004256857600000051
Patent Text Reader

Abstract

The invention discloses a light-absorbing heat-resistant plastic masterbatch containing mica iron oxide and a preparation method thereof, and belongs to the technical field of plastic masterbatch preparation. The invention is used to solve the technical problem that mica iron oxide doped in polyolefin plastics in the prior art leads to poor mechanical properties of plastics due to the influence of weak interfaces and the high temperature resistance and ultraviolet light absorption and anti-aging performance of plastics need to be further improved. The light-absorbing heat-resistant plastic masterbatch containing mica iron oxide is prepared by mixing polypropylene, heat-resistant additives, mica iron oxide additives and auxiliary additives in a weight ratio of 7:2:2:0.3, and then melt-extruding and granulating through a twin-screw; the heat-resistant additive is a styrene-acrylonitrile copolymer. The invention not only reduces the weak interface between mica iron oxide and polyolefin plastics, improves the mechanical properties of plastics, but also improves the high temperature resistance and ultraviolet light absorption performance of plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic masterbatch preparation, and in particular to light-absorbing heat-resistant plastic masterbatch containing mica iron oxide and a preparation method thereof. Background Art

[0002] With the development of economy, the application of injection molding products has also been rapidly developed. The production of injection molding products uses a large number of plastic raw materials such as PP, PE, ABS, etc., but these plastic raw materials alone cannot produce high-quality and low-cost products. Masterbatch needs to be added to improve the performance of injection molding products. High-performance masterbatch plays a great role in improving the performance of injection molding products.

[0003] Mica iron oxide, whose main chemical component is α-Fe2O3, is resistant to high temperatures, non-toxic, not easy to react with acids, alkalis, salts, etc., and is not damaged by nature such as sunlight, rain, dew, and snow. It can reflect and absorb ultraviolet rays, effectively protect objects from corrosion, and is particularly effective in resisting powdering. It is known as a natural environmentally friendly pigment and is widely used in coatings and plastics.

[0004] Micaceous iron oxide in the prior art is usually used to replace titanium dioxide and is added to plastic products. Micaceous iron oxide has poor compatibility with polyolefin plastics, resulting in a weak interface in the plastic, which means that the mechanical properties of the plastic need to be further improved. In order to improve the high temperature resistance and UV absorption anti-aging performance of polyolefin plastics, the usual practice is to add high temperature resistant polymers and UV absorbers to polyolefin plastics. However, the UV absorber is mixed with the polyolefin plastic by simple physical doping, which easily leads to uneven dispersion and migration and loss from the plastic, resulting in the high temperature resistance and UV absorption anti-aging performance of the polyolefin to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a light-absorbing heat-resistant plastic masterbatch containing mica iron oxide and a preparation method thereof, so as to solve the technical problems in the prior art that the compatibility between mica iron oxide and polyolefin plastic is poor, resulting in a weak interface in the plastic, leading to poor mechanical properties of the plastic and the phenomenon of uneven dispersion and migration and loss from the plastic when the high-temperature resistant polymer and ultraviolet light absorber are mixed with the polyolefin plastic by simple physical doping, and the high-temperature resistance and ultraviolet light absorption and anti-aging properties of the plastic need to be further improved.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The light-absorbing heat-resistant plastic masterbatch containing mica iron oxide is prepared by uniformly mixing polypropylene, a heat-resistant additive, a mica iron oxide additive and an auxiliary additive in a weight ratio of 7:2:2:0.3, and then melting and extruding the mixture through a twin-screw extruder and granulating the mixture.

[0009] The heat-resistant additive is styrene-acrylonitrile copolymer, and the auxiliary additive is composed of a dispersant, an antioxidant, a lubricant and a plasticizer in a weight ratio of 2:1:1:1;

[0010] The mica iron oxide additive is prepared by reacting mica iron oxide with KH-570, and after the mica iron oxide is modified, a free radical polymerization reaction occurs with ethyl acrylate, butyl methacrylate, allyl alcohol, modified mica iron oxide and a modified light absorber in an initiator and emulsifier environment to generate a polyolefin-coated mica iron oxide powder.

[0011] Furthermore, the modified light absorber is prepared by a substitution addition reaction between 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and acryloyl chloride in a tetrahydrofuran system with triethylamine as an acid-binding agent, and grafting acryloyl chloride onto 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.

[0012] Furthermore, the dispersant is one or more of zinc stearate, barium stearate, and magnesium stearate; the antioxidant is one or more of tea polyphenols, butylated hydroxyanisole, butylated hydroxytoluene, and tert-butylhydroquinone; the lubricant is one or more of glycerol trihydroxystearate, polyethylene wax, and microcrystalline paraffin; the plasticizer is one or more of dioctyl phthalate, diester phthalate, diisodecyl phthalate, dioctyl adipate, and dioctyl azelate. One or more, the temperatures of the multiple temperature sections of the twin-screw extruder barrel from the feed end to the discharge end are 230°C, 240°C, 250°C, 250°C and 240°C respectively, and the screw speed is 20r / min. After extrusion by the twin-screw extruder, the sample is water-cooled and then cut into wet plastic masterbatch by a pelletizer at a speed of 200r / min. The wet plastic masterbatch is transferred to a drying oven at a temperature of 75-85°C and vacuum-dried to constant weight to obtain plastic masterbatch.

[0013] The preparation method of light-absorbing heat-resistant plastic masterbatch containing mica iron oxide comprises the following steps:

[0014] S1. Add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, triethylamine and tetrahydrofuran into a three-necked flask, raise the temperature of the three-necked flask to 55-65°C, stir until the system is dissolved, slowly drop 50 wt% acryloyl chloride tetrahydrofuran solution into the three-necked flask, and keep the temperature for reaction for 8-10 hours, and post-treat to obtain a modified light absorber;

[0015] The synthetic reaction principle of the modified light absorber is:

[0016]

[0017] S2, add OP-10, sodium dodecylbenzene sulfonate and purified water into a three-necked flask, stir until the system is dissolved, add 0.3M sodium hydroxide solution into the three-necked flask, adjust the pH of the system to 8-10, and obtain an emulsion;

[0018] S3, adding the emulsion, modified mica iron oxide, modified light absorber and initiator into a three-necked flask and stirring, raising the temperature of the three-necked flask to 75-85°C, slowly dropping a droplet consisting of ethyl acrylate, butyl methacrylate and acryl alcohol into the three-necked flask, and after the dropping is complete, heat-retaining the reaction for 3-5 hours, and post-treating to obtain the mica iron oxide additive;

[0019] The synthetic reaction principle of mica iron oxide additive is:

[0020]

[0021] S4, uniformly mix the polypropylene, heat-resistant additives, mica iron oxide additives and auxiliary additives, add them into a screw extruder, melt-extrude, and granulate to obtain plastic masterbatch.

[0022] The further preparation method of the modified mica iron oxide comprises the following steps:

[0023] A1, adding mica iron oxide, water and abrasive into a ball mill, and performing ball milling to obtain mica iron oxide powder;

[0024] A2. Add mica iron oxide powder, ethanol and water into a three-necked flask and ultrasonically disperse for 30-50 minutes. Transfer the three-necked flask to an iron stand with mechanical stirring and stir. Add ammonia water into the three-necked flask to adjust the pH of the system to 8-9. Increase the temperature of the three-necked flask to 50-60°C, drop KH-570 into the three-necked flask, keep warm for reaction for 30-50 minutes, and obtain modified mica iron oxide by post-treatment.

[0025] The synthetic reaction principle of modified mica iron oxide is:

[0026]

[0027] Furthermore, in step A1, the weight ratio of mica iron oxide, abrasive and water is 10:0.2:12, the abrasive is composed of silicon carbide, iron oxide and stearic acid in a weight ratio of 2:1:2, the ball-to-material ratio in the ball mill is 8:1, the rotation speed of the ball mill is 300-500r / min, and the ball milling time is 2-3h. After the ball milling is completed, the filter is filtered, the filter cake is washed with purified water and ethanol in turn, and the filter cake is transferred to a drying oven at a temperature of 60-80°C and vacuum dried to constant weight, and crushed to obtain mica iron oxide powder.

[0028] Furthermore, in step A2, the weight ratio of mica iron oxide powder, ethanol, water and KH-570 is 2:5:3:0.6, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed with purified water and ethanol, and the filter cake is transferred to a drying oven at a temperature of 60-70°C and vacuum dried to constant weight to obtain modified mica iron oxide.

[0029] Furthermore, the molar ratio of the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole to acryloyl chloride is 1:1, the weight of the tetrahydrofuran is 3 times the weight of the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, the amount of the triethylamine is 0.3 times the weight of the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and the post-treatment operation includes: after the reaction is completed, the three-necked flask is kept at 55-65° C. and the tetrahydrofuran is evaporated under reduced pressure, purified water is added to the three-necked flask, stirred for 10-20 minutes, filtered, and the filter cake is recrystallized with ethanol to obtain a modified light absorber.

[0030] Furthermore, the weight ratio of the OP-10, sodium dodecylbenzene sulfonate and purified water is 1:0.5:85.

[0031] Furthermore, the weight ratio of the emulsion, modified mica iron oxide, modified light absorber, initiator, ethyl acrylate, butyl methacrylate, and acryl alcohol is 10:2:1:0.1:1:1.4:1.1, the initiator is potassium persulfate or azobisisobutyronitrile, and the post-treatment operation includes: after the reaction is completed, adding 15wt% sodium chloride solution to a three-necked flask, stirring until the system is clarified, filtering, washing the filter cake with purified water, transferring the filter cake to a drying oven at a temperature of 65-75°C for vacuum drying to constant weight, and crushing to obtain a mica iron oxide additive.

[0032] The present invention has the following beneficial effects:

[0033] 1. In the preparation process of the light-absorbing heat-resistant plastic masterbatch of the present invention, after ball-milling mica iron oxide into powder, the mica iron oxide powder reacts with KH-570 in an alkaline environment, so that the siloxane bonds on KH-570 are hydrolyzed and react with the surface oxygen-containing functional groups of the mica iron oxide powder, KH-570 is grafted onto the mica iron oxide powder, and the mica iron oxide powder is modified to prepare modified mica iron oxide; mica iron oxide itself has a flaky structure, and the average fineness of the mica iron oxide after grinding can reach less than 10 microns, and the layered structure of the particles can be well maintained, thereby improving the ability of mica iron oxide to reflect and absorb ultraviolet rays; by modifying the mica iron oxide powder, a silane coupling agent with an olefin structure is grafted on the outside of the mica iron oxide particles, thereby improving the polarity of the modified mica iron oxide, thereby improving the dispersibility of the mica iron oxide in polyolefin plastics, thereby improving the ability of polyolefin plastics to reflect and absorb ultraviolet rays.

[0034] 2. In the preparation process of the light-absorbing heat-resistant plastic masterbatch of the present invention, the phenolic hydroxyl group on 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and the acyl chloride on acryloyl chloride undergo substitution addition reaction, so that acryloyl chloride is grafted onto 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and an olefin double bond is formed on 2-(2'-hydroxy-5'-methylphenyl)benzotriazole. The modified mica iron oxide, the modified light absorber, ethyl acrylate, butyl methacrylate, and acryl alcohol are placed in an emulsion environment, and the olefin double bond is broken by the action of an initiator to generate a free radical reaction to generate a polyolefin, which is coated on the outside of the mica iron oxide to prepare a polyolefin-coated mica iron oxide additive; the polyolefin coated on the outside of the mica iron oxide is similar in structure to polypropylene, and the mica iron oxide additive is further improved. The invention discloses a novel nanostructured carbon nanotube polymer, which can improve the dispersion of the nanostructured carbon nanotube polymer in polypropylene and generate physical crosslinking with polypropylene, thereby reducing the weak interface of the nanostructured carbon nanotube polymer in polypropylene and improving the mechanical properties of the plastic. The nanostructured carbon nanotube polymer can absorb ultraviolet rays and release the absorbed ultraviolet rays in the form of heat energy, thereby improving the ability of the plastic to absorb and convert ultraviolet rays. In addition, the nanostructured carbon nanotube polymer can crosslink with polyolefin in the form of chemical bonds, thereby preventing the nanostructured carbon nanotube polymer from aging and migrating from the plastic and ensuring the ability of the plastic to absorb ultraviolet rays. The iron oxide structure of the nanostructured carbon nanotube polymer itself enables it to have good thermal conductivity and improve the overall heat resistance of the plastic. Adding styrene-acrylonitrile copolymer as a heat-resistant additive to the plastic masterbatch can further improve the heat resistance of the plastic masterbatch. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment provides a method for preparing a light-absorbing heat-resistant plastic masterbatch containing mica iron oxide, comprising the following steps:

[0038] S1. Mica iron oxide modification treatment

[0039] Weigh by weight: 100 g of mica iron oxide, 120 g of water, 0.8 g of silicon carbide, 0.4 g of iron oxide and 0.8 g of stearic acid, add them into a ball mill, set the ball-to-material ratio of the ball mill to 8:1, the speed of the ball mill to 300 r / min, and the ball milling time to 2 h. After the ball milling is completed, filter, wash the filter cake with purified water and ethanol in turn, transfer the filter cake to a drying oven at a temperature of 60° C., vacuum dry to constant weight, and crush to obtain mica iron oxide powder;

[0040] Weigh by weight: 80g of mica iron oxide powder, 200g of ethanol, and 120g of water are added to a three-necked flask and ultrasonically dispersed for 30min. The three-necked flask is transferred to an iron stand with mechanical stirring for stirring. Ammonia water is added to the three-necked flask to adjust the system pH to 8. The temperature of the three-necked flask is increased to 50°C. 24g of KH-570 is added dropwise to the three-necked flask, and the reaction is kept warm for 30min. The temperature of the three-necked flask is lowered to room temperature, and the filter cake is filtered, and the filter cake is washed with purified water and ethanol. The filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain modified mica iron oxide;

[0041] S2. Preparation of modified light absorber

[0042] Weigh by weight: 100 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 30 g of triethylamine, and 300 g of tetrahydrofuran are added to a three-necked flask. The temperature of the three-necked flask is raised to 55° C. and stirred until the system is dissolved. 80.4 g of a 50 wt% acryloyl chloride tetrahydrofuran solution is slowly added dropwise to the three-necked flask. After the addition is complete, the mixture is kept warm for 8 hours. The three-necked flask is kept warm at 55° C. and the tetrahydrofuran is evaporated under reduced pressure. Purified water is added to the three-necked flask, stirred for 10 minutes, and filtered. The filter cake is recrystallized with ethanol to obtain a modified light absorber.

[0043] S3. Preparation of emulsion

[0044] OP-10, sodium dodecylbenzene sulfonate and purified water were added into a three-necked flask at a weight ratio of 1:0.5:85, and stirred until the system was dissolved. A 0.3 M sodium hydroxide solution was added into the three-necked flask to adjust the pH of the system to 8 to obtain an emulsion;

[0045] S4. Preparation of mica iron oxide additive

[0046] Weigh by weight: 200g of emulsion, 40g of modified mica iron oxide, 20g of modified light absorber, and 2g of potassium persulfate are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 75°C. A drop solution consisting of 20g of ethyl acrylate, 28g of butyl methacrylate, and 22g of allyl alcohol is slowly added dropwise to the three-necked flask. After the addition is complete, the mixture is kept warm for 3-5h. A 15wt% sodium chloride solution is added to the three-necked flask and stirred until the system is clarified. The mixture is filtered, the filter cake is washed with purified water, and then the filter cake is transferred to a drying oven at a temperature of 65°C and vacuum dried to constant weight, and crushed to obtain a mica iron oxide additive.

[0047] S5. Preparation of plastic masterbatch

[0048] Weigh by weight: 700g of polypropylene, 200g of styrene-acrylonitrile copolymer, 200g of mica iron oxide additive, 12g of zinc stearate, 6g of tea polyphenols, 6g of glyceryl trihydroxystearate and 6g of dioctyl phthalate, mix well, and add to a screw extruder. The temperatures of multiple temperature sections of the twin-screw extruder barrel from the feed end to the discharge end are 230°C, 240°C, 250°C, 250°C and 240°C, respectively, and the screw speed is 20r / min. After extrusion by the twin-screw extruder, the sample is water-cooled and cut into wet plastic masterbatch by a pelletizer at a speed of 200r / min. The wet plastic masterbatch is transferred to a drying oven at a temperature of 75°C and vacuum-dried to constant weight to obtain a plastic masterbatch.

[0049] Example 2

[0050] This embodiment provides a method for preparing a light-absorbing heat-resistant plastic masterbatch containing mica iron oxide, comprising the following steps:

[0051] S1. Mica iron oxide modification treatment

[0052] Weigh by weight: 100 g of mica iron oxide, 120 g of water, 0.8 g of silicon carbide, 0.4 g of iron oxide and 0.8 g of stearic acid, add them into a ball mill, set the ball-to-material ratio of the ball mill to 8:1, the speed of the ball mill to 400 r / min, and the ball milling time to 2.5 h. After the ball milling is completed, filter, wash the filter cake with purified water and ethanol in turn, transfer the filter cake to a drying oven at a temperature of 70° C., vacuum dry to constant weight, and crush to obtain mica iron oxide powder;

[0053] Weigh by weight: 80g of mica iron oxide powder, 200g of ethanol, and 120g of water are added to a three-necked flask and ultrasonically dispersed for 40min. The three-necked flask is transferred to an iron stand with a mechanical stirrer for stirring. Ammonia water is added to the three-necked flask to adjust the system pH to 8.5. The temperature of the three-necked flask is increased to 55°C. 24g of KH-570 is added dropwise to the three-necked flask, and the reaction is kept warm for 40min. The temperature of the three-necked flask is lowered to room temperature, and the filter cake is filtered, and the filter cake is washed with purified water and ethanol. The filter cake is transferred to a drying oven at a temperature of 65°C and vacuum dried to constant weight to obtain modified mica iron oxide;

[0054] S2. Preparation of modified light absorber

[0055] Weigh by weight: 100 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 30 g of triethylamine, and 300 g of tetrahydrofuran are added to a three-necked flask. The temperature of the three-necked flask is raised to 60° C. and stirred until the system is dissolved. 80.4 g of a 50 wt% acryloyl chloride tetrahydrofuran solution is slowly added dropwise to the three-necked flask. After the addition is complete, the reaction is kept warm for 9 hours. The three-necked flask is kept warm at 60° C. and the tetrahydrofuran is evaporated under reduced pressure. Purified water is added to the three-necked flask, stirred for 15 minutes, and filtered. The filter cake is recrystallized with ethanol to obtain a modified light absorber.

[0056] S3. Preparation of emulsion

[0057] OP-10, sodium dodecylbenzene sulfonate and purified water were added into a three-necked flask at a weight ratio of 1:0.5:85, and stirred until the system was dissolved. A 0.3 M sodium hydroxide solution was added into the three-necked flask, and the pH of the system was adjusted to 9 to obtain an emulsion.

[0058] S4. Preparation of mica iron oxide additive

[0059] Weigh by weight: 200 g of emulsion, 40 g of modified mica iron oxide, 20 g of modified light absorber, and 2 g of azobisisobutyronitrile are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 80° C. A drop solution consisting of 20 g of ethyl acrylate, 28 g of butyl methacrylate, and 22 g of allyl alcohol is slowly added dropwise to the three-necked flask. After the addition is complete, the mixture is kept warm for 4 hours. A 15 wt % sodium chloride solution is added to the three-necked flask and stirred until the system is clarified. The mixture is filtered, the filter cake is washed with purified water, and then the filter cake is transferred to a drying oven at a temperature of 70° C. and vacuum dried to constant weight, and crushed to obtain a mica iron oxide additive.

[0060] S5. Preparation of plastic masterbatch

[0061] Weigh by weight: 700g of polypropylene, 200g of styrene-acrylonitrile copolymer, 200g of mica iron oxide additive, 12g of barium stearate, 6g of butylated hydroxyanisole, 6g of polyethylene wax and 6g of distear phthalate, mix well, and add to a screw extruder. The temperatures of multiple temperature sections of the twin-screw extruder barrel from the feed end to the discharge end are 230°C, 240°C, 250°C, 250°C and 240°C, respectively, and the screw speed is 20r / min. After extrusion by the twin-screw extruder, the sample is water-cooled and cut into wet plastic masterbatch by a pelletizer at a speed of 200r / min. The wet plastic masterbatch is transferred to a drying oven at a temperature of 80°C and vacuum-dried to constant weight to obtain a plastic masterbatch.

[0062] Example 3

[0063] This embodiment provides a method for preparing a light-absorbing heat-resistant plastic masterbatch containing mica iron oxide, comprising the following steps:

[0064] S1. Mica iron oxide modification treatment

[0065] Weigh by weight: 100 g of mica iron oxide, 120 g of water, 0.8 g of silicon carbide, 0.4 g of iron oxide and 0.8 g of stearic acid, add them into a ball mill, set the ball-to-material ratio of the ball mill to 8:1, the speed of the ball mill to 500 r / min, and the ball milling time to 3 h. After the ball milling is completed, filter, wash the filter cake with purified water and ethanol in turn, transfer the filter cake to a drying oven at a temperature of 80° C., vacuum dry to constant weight, and crush to obtain mica iron oxide powder;

[0066] Weigh by weight: 80g of mica iron oxide powder, 200g of ethanol, and 120g of water are added to a three-necked flask and ultrasonically dispersed for 50min. The three-necked flask is transferred to an iron stand with a mechanical stirrer for stirring. Ammonia water is added to the three-necked flask to adjust the system pH to 9. The temperature of the three-necked flask is increased to 60°C. 24g of KH-570 is added dropwise to the three-necked flask, and the reaction is kept warm for 50min. The temperature of the three-necked flask is lowered to room temperature, and the filter cake is filtered, and the filter cake is washed with purified water and ethanol. The filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain modified mica iron oxide;

[0067] S2. Preparation of modified light absorber

[0068] Weigh by weight: 100 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 30 g of triethylamine, and 300 g of tetrahydrofuran are added to a three-necked flask, the temperature of the three-necked flask is raised to 65° C., and the system is stirred until it is dissolved. 80.4 g of a 50 wt% acryloyl chloride tetrahydrofuran solution is slowly added dropwise to the three-necked flask. After the addition is complete, the reaction is kept warm for 10 hours. The three-necked flask is kept warm at 65° C. and the tetrahydrofuran is evaporated under reduced pressure. Purified water is added to the three-necked flask, and the mixture is stirred for 20 minutes. The filter cake is then filtered and recrystallized with ethanol to obtain a modified light absorber.

[0069] S3. Preparation of emulsion

[0070] OP-10, sodium dodecylbenzene sulfonate and purified water were added into a three-necked flask at a weight ratio of 1:0.5:85, and stirred until the system was dissolved. A 0.3 M sodium hydroxide solution was added into the three-necked flask, and the pH of the system was adjusted to 10 to obtain an emulsion;

[0071] S4. Preparation of mica iron oxide additive

[0072] Weigh by weight: 200 g of emulsion, 40 g of modified mica iron oxide, 20 g of modified light absorber, and 2 g of potassium persulfate are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 85° C. A droplet consisting of 20 g of ethyl acrylate, 28 g of butyl methacrylate, and 22 g of allyl alcohol is slowly added dropwise to the three-necked flask. After the addition is complete, the mixture is kept warm for 5 h. A 15 wt % sodium chloride solution is added to the three-necked flask and stirred until the system is clarified. The mixture is filtered, the filter cake is washed with purified water, and then the filter cake is transferred to a drying oven at a temperature of 75° C. and vacuum dried to constant weight, and crushed to obtain a mica iron oxide additive.

[0073] S5. Preparation of plastic masterbatch

[0074] Weigh by weight: 700g of polypropylene, 200g of styrene-acrylonitrile copolymer, 200g of mica iron oxide additive, 12g of magnesium stearate, 6g of tert-butylhydroquinone, 6g of microcrystalline wax and 6g of dioctyl adipate, mix well, and add to a screw extruder. The temperatures of multiple temperature sections of the twin-screw extruder barrel from the feed end to the discharge end are 230°C, 240°C, 250°C, 250°C and 240°C, respectively, and the screw speed is 20r / min. After extrusion by the twin-screw extruder, the sample is water-cooled and cut into wet plastic masterbatch by a pelletizer at a speed of 200r / min. The wet plastic masterbatch is transferred to a drying oven at a temperature of 85°C and vacuum-dried to constant weight to obtain a plastic masterbatch.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 3 is that the modified mica iron oxide in step S4 is replaced by an equal amount of mica iron oxide powder in step S1.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 3 is that step S4 is eliminated, and the micaceous iron oxide additive in step S5 is replaced by an equal amount of micaceous iron oxide powder.

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 3 is that no modified light absorber is added in step S4, and no styrene-acrylonitrile copolymer is added in step S5.

[0081] Performance Testing:

[0082] The plastic masterbatches prepared in Examples 1-3 and Comparative Examples 1-3 were melt-mixed with polyolefin plastics in a weight ratio of 1:5 to prepare plastic specimens. The heat resistance, UV resistance and mechanical properties of the plastic specimens prepared by doping the plastic masterbatches in Examples 1-3 and Comparative Examples 1-3 were tested. The mechanical properties of the plastics were determined by referring to the standard GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General" to determine the tensile strength of the specimens and the standard GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test" to determine the notched impact strength of the specimens; the heat resistance was determined by referring to the standard GB / T 1633-2000 "Determination of Vicat softening temperature (VST) of thermoplastics" to test the Vicat softening temperature of the specimens; the UV resistance was determined by referring to the standard GB / T 16422.3-2022 "Plastics Laboratory Light Source Exposure Test Method Part 3: Fluorescent UV Lamp" determines the UV resistance of the test piece. The specific test results are shown in the table below:

[0083]

[0084] Data Analysis:

[0085] The performance test data of Examples 1-3 are better than those of Comparative Examples 1-3, indicating that the plastic masterbatch prepared by the present invention can effectively improve the mechanical properties, high temperature resistance and ultraviolet radiation resistance of polypropylene plastics;

[0086] The performance data of comparative example 1-2 are compared with the data of embodiment 1-3. The mechanical properties and Vicat softening temperature of comparative example 1-2 are lower than those of embodiment 1-3, indicating that the present invention modifies the mica iron oxide powder to prepare the mica iron oxide additive with polyolefin coating, which can effectively improve the dispersibility of the mica iron oxide powder in polypropylene and the crosslinking between the mica iron oxide powder and the polypropylene plastic, and improve the high temperature resistance of the plastic;

[0087] The performance data of comparative example 3 are compared with the data of embodiments 1-3. The mechanical properties of comparative example 3 are not much different from those of embodiments 1-3, but its Vicat softening temperature and ultraviolet radiation resistance are poor, indicating that the styrene-acrylonitrile copolymer added to the plastic masterbatch can play a synergistic role with mica iron oxide to improve the high temperature resistance of the plastic. By adding a modified light absorber in step S4, the ultraviolet light absorption and anti-aging properties of the plastic can be effectively improved.

[0088] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0089] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0090] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A light-absorbing heat-resistant plastic masterbatch containing mica iron oxide, characterized in that: The polypropylene, heat-resistant additive, mica iron oxide additive and auxiliary additive are uniformly mixed in a weight ratio of 7:2:2:0.3, and then melt-extruded and granulated by a twin-screw extruder. The heat-resistant additive is styrene-acrylonitrile copolymer, and the auxiliary additive is composed of a dispersant, an antioxidant, a lubricant and a plasticizer in a weight ratio of 2:1:1:1; The mica iron oxide additive is prepared by reacting mica iron oxide with KH-570 to modify the mica iron oxide, and then reacting with ethyl acrylate, butyl methacrylate, allyl alcohol, and a modified light absorber in an initiator and emulsion environment to generate a polyolefin-coated mica iron oxide powder; Mica iron oxide additives are processed by the following steps: S1. Add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, triethylamine and tetrahydrofuran into a three-necked flask, raise the temperature of the three-necked flask to 55-65°C, stir until the system is dissolved, slowly drop 50wt% acryloyl chloride tetrahydrofuran solution into the three-necked flask, and keep the temperature for reaction for 8-10h, and post-treat to obtain a modified light absorber; S2, add OP-10, sodium dodecylbenzene sulfonate and purified water into a three-necked flask, stir until the system is dissolved, add 0.3M sodium hydroxide solution into the three-necked flask, adjust the pH of the system to 8-10, and obtain an emulsion; S3. Add the emulsion, modified mica iron oxide, modified light absorber and initiator into a three-necked flask and stir. Raise the temperature of the three-necked flask to 75-85°C. Slowly drop a drop of ethyl acrylate, butyl methacrylate and allyl alcohol into the three-necked flask. After the drop is added, heat and react for 3-5 hours. Perform post-treatment to obtain the mica iron oxide additive.

2. The light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to claim 1, characterized in that: The modified light absorber is prepared by a substitution addition reaction between 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and acryloyl chloride in a tetrahydrofuran system with triethylamine as an acid-binding agent, and grafting acryloyl chloride onto 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.

3. The light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to claim 1, characterized in that: The molar ratio of the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole to acryloyl chloride is 1:1, the weight of the tetrahydrofuran is 3 times the weight of the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and the amount of the triethylamine is 0.3 times the weight of the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.

4. The light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to claim 1, characterized in that: The weight ratio of the OP-10, sodium dodecylbenzene sulfonate and purified water is 1:0.5:

85.

5. The light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to claim 1, characterized in that: The weight ratio of the emulsion, modified mica iron oxide, modified light absorber, initiator, ethyl acrylate, butyl methacrylate and acryl alcohol is 10:2:1:0.1:1:1.4:1.1, and the initiator is potassium persulfate or azobisisobutyronitrile.

6. The method for preparing the light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to any one of claims 1 to 5, characterized in that: The preparation method of the light-absorbing heat-resistant plastic masterbatch containing micaceous iron oxide is as follows: polypropylene, heat-resistant additives, micaceous iron oxide additives and auxiliary additives are uniformly mixed, added into a screw extruder, melt-extruded, granulated, and the plastic masterbatch is obtained.

7. The method for preparing the light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to claim 6, characterized in that: The preparation method of the modified mica iron oxide comprises the following steps: A1, adding mica iron oxide, water and abrasive into a ball mill, and performing ball milling to obtain mica iron oxide powder; A2. Add mica iron oxide powder, ethanol and water into a three-necked flask and ultrasonically disperse for 30-50 minutes. Transfer the three-necked flask to an iron stand with mechanical stirring and stir. Add ammonia water into the three-necked flask to adjust the pH of the system to 8-9. Increase the temperature of the three-necked flask to 50-60°C, drop KH-570 into the three-necked flask, keep warm and react for 30-50 minutes, and post-treat to obtain modified mica iron oxide.

8. The method for preparing the light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to claim 7, characterized in that: In step A1, the weight ratio of mica iron oxide, abrasive and water is 10:0.2:12, the abrasive is composed of silicon carbide, iron oxide and stearic acid in a weight ratio of 2:1:2, the ball-to-material ratio in the ball mill is 8:1, the speed of the ball mill is 300-500r / min, the ball milling time is 2-3h, and after the ball milling is completed, the filter cake is filtered and washed with purified water and ethanol in turn, and the filter cake is transferred to a drying oven at a temperature of 60-80°C and vacuum dried to constant weight, and crushed to obtain mica iron oxide powder.

9. The method for preparing the light-absorbing heat-resistant plastic masterbatch containing mica iron oxide according to claim 7, characterized in that: The weight ratio of mica iron oxide powder, ethanol, water and KH-570 in step A2 is 2:5:3:0.6.

Citation Information

Patent Citations

  • Polypropylene heatproof weather-proof master batch, and preparation method and application thereof

    CN104098832A

  • Method for modifying mica iron oxide with silane coupling agent

    CN106398317A

  • Method for modifying micaceous iron oxide with silane coupling agent

    CN106398371A

  • Benzotriazole-containing reactive ultraviolet absorbent, preparation method thereof and application of absorbent

    CN109824614A

  • Modified master batch for enhancing weather resistance of polyethylene winding pipe and preparation method of modified master batch

    CN114213732A